Rhododendron in New Zealand and ex situ conservation. - MacKay M (Massey University, 2022)
This presentation outlines the New Zealand ex situ Rhododendron Conservation Project, its relationship to the Global Conservation Consortium, and practical steps that collection managers can take to support conservation.
Keywords: Rhododendron; ex situ conservation